Sunan Kalijaga Da'wah Media in the Spread of Islam in Java - Husniyah, Nur Iftitahul; Sodik, Mohamad (STAI Miftahul Ula Nganjuk, 2024)
The development of Islamic teachings in the archipelago cannot be separated from Walisongo's role. Walisongo preached and broadcast Islamic religious teachings in the land of Java in the 14th century. His missionary areas along the island of Java include Surabaya, Gresik, Tuban for East Java, Demak, Kudus, Muria in Central Java and Cirebon in West Java. The spread of Islam in Indonesia, especially the island of Java, was a success so that it was proven acceptable by the community through the da'wah method used by Wali Songo. Walisongo in spreading Islamic teachings has their own characteristics, this is done so that Islam can easily blend in and be accepted by the Javanese people. The spread of Islam by Walisongo used a cultural approach by means of acculturation of local cultural arts packed with Islam such as wayang, Javanese songs, gamelan, traditional ceremonies combined with Islam. Besides that, with the expertise of the Wali using old elements (Hindu-Buddhist) as a medium for their da'wah and little by little incorporating the values ​​of Islamic religious teachings into these elements or it can be called the syncretism method which means mixing as elements of a school or ideology so that the form different abstracts form harmony. The purpose of this study was to find out the media of Sunan Kalijaga's preaching in the spread of Islam in Java. Sunan Kalijaga who creates works of art using nuances that can be understood by Javanese people, namely Hinduism and Buddhism. This is one of the roles played by Sunan Kalijaga in preaching the process of Islamization with a cultural approach. The research method in this study is a literature study or library research aimed at collecting information and data with various kinds of library instruments, both books, journals, files and others. Furthermore, the results of this study indicate that in the process of spreading Islam, Sunan Kalijaga used several including the media of wayang kulit, mysticism, gerebeg and sekaten ceremonies. In every wayang performance, Sunan Kalijaga never asks for material fees. As payment, Sunan Kalijaga invited all the people who were present to watch the shahada together to admit that there is no God but Allah and the Prophet Muhammad is the messenger of Allah. Keywords: The Spread of Islam, Da'wah Sunan Kalijaga